Takes two to tax. On fair taxation of the digital economy - Jacques Delors Institut; Schneemelcher, Pola (Berlin, 2018)
"The ongoing digital transformation poses enormous challenges to current tax law. This is, because value creation through intangibles raises problems to two core paradigms of international tax rules: where to tax and what to tax. In order to solve these problems, the European Commission published two proposals, a so-called interim tax and a comprehensive solution. In this blogpost, Pola Schneemelcher assesses the proposals and makes the case that they do not sufficiently address the crucial question of how to value data."